Manajemen Pendidikan Berbasis Nilai Hindu di Madyama Widyalaya Jnana Dharma Sastra, Buleleng - Putera, Made Devia Paramitha; Putra, I Nyoman Miarta; Raka, I Nyoman; Purnomo, I Made Bagus Andi (Cetta: Jurnal Ilmu Pendidikan, 2025)
Educational management consists of planning, organization, and control in managing the education system effectively. In the context of widyalaya education, the main challenge lies in the lack of human resources, infrastructure, and community support. The study aims to disseminate and implement the application of Hindu values-based management at Madyama Widyalaya Jnana Dharma Sastra, thereby contributing to a comprehensive understanding of the integration of Hindu teaching principles in educational management, including aspects of curriculum, leadership, educators, students, and facilities and infrastructure. This study is qualitative with a case study approach, focusing on Hindu-based educational management, with data collected through participatory observation, in-depth interviews, documentation studies, and FGDs. This study examines educational management based on Hindu religious values ​​at Madyama Widyalaya Jnana Dharma Sastra, Buleleng. This institution implements Fayol's management functions synergized with Hindu teachings, such as Tri Hita Karana in planning and karma yoga in supervision. The organizational structure emphasizes the concept of swadharma and satyam-ahimsa leadership. Although internal coordination is running well, external relations with the Buleleng Education and Culture Office overcome challenges. The main challenges include policy dualism, bureaucracy, and resource constraints. This study is a pioneer in combining modern management theory with Vedic values, resulting in a holistic model that is contextual but requires adjustment to the national education system. The novelty of the study entitled "Education Management Based on Hindu Religious Education Values ​​in Madyama Widyalaya Jnana Dharma Sastra" lies in its approach that systematically integrates Hindu teaching values ​​such as dharma (truth/duty), tattwa (philosophy), susila (ethics), and ceremony (ritual) into all aspects of formal secondary Hindu education management.